Characteristics of Gut Microbiota in Children With Biliary Atresia After Liver Transplantation - Song, Wei; Sun, Li-Ying; Zhu, Zhi-Jun; Wei, Lin; Qu, Wei; Zeng, Zhi-Gui; Yang, Yun-Sheng (Frontiers in Physiology, 2021)
Background & Aims: Biliary atresia (BA) is an idiopathic neonatal cholestasis and is the most common indication in pediatric liver transplantation (LT). Previous studies have suggested that the gut microbiota (GM) in BA is disordered. However, the effect of LT on gut dysbiosis in patients with BA has not yet been elucidated. Methods: Patients with BA (n=16) and healthy controls (n=10) were recruited. In the early life of children with BA, Kasai surgery is a typical procedure for restoring bile flow. According to whether BA patients had previously undergone Kasai surgery, we divided the post-LT patients into the with-Kasai group (n=8) and non-Kasai group (n=8). Fecal samples were collected in both the BA and the control group; among BA patients, samples were obtained again six months after LT. A total of 40 fecal samples were collected, of which 16 were pre-LT, 14 were post-LT (8 were with-Kasai, 6 were non-Kasai), and 10 were from the control group. Metagenomic sequencing was performed to evaluate the GM. Results: The Kruskal-Wallis test showed a statistically significant difference in the number of genes between the pre-LT and the control group, the pre-LT and the post-LT group (P < 0.05), but no statistical difference between the post-LT and the control group. Principal coordinate analysis also showed that the microbiome structure was similar between the post-LT and control group (P > 0.05). Analysis of the GM composition showed a significant decrease in Serratia, Enterobacter, Morganella, Skunalikevirus, and Phifllikevirus while short chain fatty acid (SCFA)-producing bacteria such as Roseburia, Blautia, Clostridium, Akkermansia, and Ruminococcus were increased after LT (linear discriminant analysis > 2, P < 0.05). However, they still did not reach the normal control level. Concerning functional profiles, lipopolysaccharide metabolism, multidrug resistance, polyamine biosynthesis, GABA biosynthesis, and EHEC/EPEC pathogenicity signature were more enriched in the post-LT group compared with the control group. Prior Kasai surgery had a specific influence on the postoperative GM. Conclusions: LT partly improved the GM in patients with BA, which provided new insight into understanding the role of LT in BA.